Synthesis of water-soluble polycarboxylates on the base of phthalic anhydride - Gladii, Andrii; Bereza, Vasyl; Tsiupko, Fedir; Yatchyshyn, Yosyp (Видавництво Львівської політехніки, 2013)
The process of synthesis (meth)acrylic monomers with carboxyl group near aromatic nucleus by reacting of phthalic anhydride (PA) and hydroxypolyoxyalkylen (meth) acrylate are investigated. The basic laws of process of non-catalytic acylation of hydroxyethylmethacrylate (Bisomer HEMA) and hexapropyleneglycolmonoacrylate (Bisomer PPA6) by phthalic anhydride are found. The values of the activation energy (EA) for examined reaction systems are calculated on the base of obtained kinetic parameters. The effect of structure of polyoxyalkylene chain on the reaction rate with PA without the use of solvents.
Keywords: phthalic anhydride; Bisomer HEMA; Bisomer PPA6; (meth)acrylic monomers; polycarboxylates; water-soluble polymers